Antibody responses elicited in mice immunized with Bacillus subtilis vaccine strains expressing Stx2B subunit of enterohaemorragic Escherichia coli O157:H7 - Gomes, P. A. D. P. (2009)
No effective vaccine or immunotherapy is presently available for patients with the hemolytic uremic syndrome (HUS) induced by Shiga-like toxin (Stx) produced by enterohaemorragic Escherichia coli (EHEC) strains, such as those belonging to the O157:H7 serotype. In this work we evaluated the performance of Bacillus subtilis strains, a harmless spore former gram-positive bacterium species, as a vaccine vehicle for the expression of Stx2B subunit (Stx2B). A recombinant B. subtilis vaccine strain expressing Stx2B under the control of a stress inducible promoter was delivered to BALB/c mice via oral, nasal or subcutaneous routes using both vegetative cells and spores. Mice immunized with vegetative cells by the oral route developed low but specific anti-Stx2B serum IgG and fecal IgA responses while mice immunized with recombinant spores developed anti-Stx2B responses only after administration via the parenteral route. Nonetheless, serum anti-Stx2B antibodies raised in mice immunized with the recombinant B. subtilis strain did not inhibit the toxic effects of the native toxin, both under in vitro and in vivo conditions, suggesting that either the quantity or the quality of the induced immune response did not support an effective neutralization of Stx2 produced by EHEC strains.